(untitled) (Nuntius Antiquus, 2014)
In the study we analyse comparatively selected fragments from Georgics IV and De re rustica (Book IX) in order to understand a little better the linguistic-literary treatment due to the distinct generic orientations the authors deliver to their works. The dominating compounding and stylistic characteristics in the texts are studied and are used as instruments to analyse (a) the constitutive particularities of the genders, didactic poetry and technical treatise (in prose), and (b) the aspects related to the construction of the particular meanings in the works. The theoretical reference marks for the text studies are: the literary genders theory, literary stylistic (referring to the Roman agrarian literature) and the history of Roman literature.